Environmental controls of suppressed fall crop productivity in an agrivoltaic solar array - Matthew A Sturchio; Dana F Russell; Jasmine Schmidt; Caroline Marschner; Antonio DiTomasso; Jinwook Kim; Steven M Grodsky (Environmental Research: Food Systems, 2025)
Globally, agrivoltaics (AV) research has revealed how microclimates created by photovoltaic (PV) panels can be leveraged to promote reciprocal benefits for agricultural land use and PV energy generation. Yet, in regions of the United States where emissions reduction laws are likely to lead to greater PV development on croplands, empirical evaluation of such co-location remain under explored. Furthermore, the most common approach to AV in the United States is one that maximizes energy generation and secondarily accommodates for agricultural management, and the controls of crop production in facilities that employ such an approach are underrepresented in the AV literature. Here, we assessed the agronomic and physiological response of two vegetable crops (radish and radicchio) with different carbon allocation patterns (belowground and aboveground, respectively) in an energy focused AV facility during a fall growing season, in New York, United States. We found that a reduction in total irradiance (−24%) within the AV array decreased total biomass in both crop types (46% and 49%), with significant alterations to root-shoot ratios in radish. Reductions in total biomass were not a result of physiological acclimation, indicating that AV crops had similar photosynthetic capacity as control crops; however, the environmental constraints imposed by energy focused AV design (i.e. reduced irradiance) limited C uptake overall. Our findings highlight the need for novel management approaches (e.g. earlier planting of AV fall crops) to help overcome yield penalties incurred by energy focused AV designs.